Reactive power control strategies for UNIFLEX-PM Converter - Pipolo, S.; Bifaretti, Stefano; Bonaiuto, V.; Tarisciotti, Luca; Zanchetta, Pericle (2016)
The paper presents various control strategies for an advanced multilevel-based power converter. A Fuzzy Logic Control, based on power balance constrains and Proportional Reactive Power control based on a more rigorous approach, have been proposed. Two different ways to assign reactive powers have been illustrated for both the control strategies and then compared in Matlab/Simulink environment accounting two active power sets. Finally, advantages and drawbacks of the proposed strategies have been highlighted.